2007
DOI: 10.1007/s10750-007-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic activity of Stratiotes aloides on phytoplankton—towards identification of allelopathic substances

Abstract: The allelopathic activity of the aquatic macrophyte, Stratiotes aloides, was determined with laboratory experiments. Active compounds exuded in the medium or present in plant tissue were extracted using standard procedures and solid phase extraction (SPE). The activity towards various cyanobacteria and chlorophytes was tested in two different bioassay systems using agar plates and liquid cultures of phytoplankton. Extracts and exudates of S. aloides affected phytoplankton growth. SPE-enriched exudates and enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 32 publications
5
26
0
1
Order By: Relevance
“…The second most effective routes were residue decomposition and leaf leachates, while leaf volatilization showed no algae growth-inhibitory effect. The similar result also had been found in the aquatic plant of water hyacinth; the root of water hyacinth could release many anticyanobacteria allelochemicals (Malik 2007;Mulderij et al 2007). The difference might be caused by the different growth environment and physiological structures of terrestrial and aquatic plants.…”
Section: Resultssupporting
confidence: 77%
“…The second most effective routes were residue decomposition and leaf leachates, while leaf volatilization showed no algae growth-inhibitory effect. The similar result also had been found in the aquatic plant of water hyacinth; the root of water hyacinth could release many anticyanobacteria allelochemicals (Malik 2007;Mulderij et al 2007). The difference might be caused by the different growth environment and physiological structures of terrestrial and aquatic plants.…”
Section: Resultssupporting
confidence: 77%
“…After 9 days, algal density began to increase, and M. aeruginosa had a greater increase rate. Similar results were obtained for other allelochemicals, while in general, cyanobacteria are considered more susceptible than green algae (Mulderij et al 2007;Zhu et al 2010). Although considerable differences have been observed among different cyanobacteria (Nakai et al 2000), as well as among green algal species (Hilt 2006), the results showed that the 16 mg L −1 group had a higher inhibition rate (about 60-70 %) during incubation process, and this concentration can be regarded as a good inhibition concentration.…”
Section: Resultssupporting
confidence: 74%
“…The use of extracts (Jasser 1995) is no proof for allelopathic interactions between S. aloides and phytoplankton in situ (Willis 1985), and it provides no direct evidence that the plant actually releases allelopathic substances. Therefore, Mulderij et al (2005aMulderij et al ( , b, 2007 used S. aloides exudates (instead of extracts) to test the plant's allelopathic activity on several phytoplankton species. Mulderij et al (2005a) observed limitation of growth and colony formation of the green alga Scenedesmus obliquus (Turpin) Kützing when exposed to S. aloides exudates.…”
Section: Introductionmentioning
confidence: 99%